2010
DOI: 10.1016/j.ijpsycho.2009.09.005
|View full text |Cite
|
Sign up to set email alerts
|

What can Event-related Potentials tell us about language, and perhaps even thought, in schizophrenia?

Abstract: Disturbances of thought and language are fundamental to schizophrenia. Cognitive behavioral and electrophysiological research has implicated problems in two distinct neurocognitive mechanisms: abnormalities in the structure and function of semantic memory, and abnormalities in combining and integrating words together to build up sentence and discourse structure. This review discusses recent electrophysiological evidence suggesting that these two deficits are not completely distinct, but rather that language im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
47
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 114 publications
4
47
0
Order By: Relevance
“…However, future studies of neuropsychological correlates of schizophrenic communication failures still may be able to reveal additional cognitive contributors related to auditory attention, or to other specific facets of cognitive functioning such as internal source memory, semantic memory, and cognitive control. [44][45][46] Psychophysiological and neuroimaging studies also have had some success in delineating the brain structures and activity involved in speech symptoms (eg, Kuperberg et al 47,48 ). These lines of research show considerable promise for identifying and localizing the brain processes involved.…”
Section: Discussionmentioning
confidence: 99%
“…However, future studies of neuropsychological correlates of schizophrenic communication failures still may be able to reveal additional cognitive contributors related to auditory attention, or to other specific facets of cognitive functioning such as internal source memory, semantic memory, and cognitive control. [44][45][46] Psychophysiological and neuroimaging studies also have had some success in delineating the brain structures and activity involved in speech symptoms (eg, Kuperberg et al 47,48 ). These lines of research show considerable promise for identifying and localizing the brain processes involved.…”
Section: Discussionmentioning
confidence: 99%
“…In other studies, language function in schizophrenia patients was investigated with semantic priming experiments using EEG showing strong evidence of abnormal semantic priming in schizophrenia based on event-related potentials (N400) [21,22]. Recently, using event-related potentials (N400), Kreher et al [23] and Kuperberg et al [24] found signs of increased spreading activation during semantic memory tasks to be associated with increasing severity of FTD. One of the major electrical sources of the event-related potential N400 is the left temporo-parietal junction (TPJ) [25,26], a region essential for the semantic system [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Memory impairment is an associated feature of schizophrenia with deficits observed across a broad range of memory systems and processes, including disturbance to semantic memory (reviews: Aleman et al, 1999;Condray, 2005;Kuperberg et al, 2010;Minzenberg et al, 2002). Semantic memory represents a person's cumulative knowledge about the world (e.g., name of the first president of the United States, defining features of tables, etc.)…”
Section: Introductionmentioning
confidence: 99%